2014
DOI: 10.1007/s13201-014-0159-9
|View full text |Cite
|
Sign up to set email alerts
|

Water quality management using statistical analysis and time-series prediction model

Abstract: This paper deals with water quality management using statistical analysis and time-series prediction model. The monthly variation of water quality standards has been used to compare statistical mean, median, mode, standard deviation, kurtosis, skewness, coefficient of variation at Yamuna River. Model validated using R-squared, root mean square error, mean absolute percentage error, maximum absolute percentage error, mean absolute error, maximum absolute error, normalized Bayesian information criterion, Ljung-B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(37 citation statements)
references
References 26 publications
2
31
0
Order By: Relevance
“…Several measures of accuracy were applied to ascertain the performance of the ARIMA models so developed such as stationary R 2 , R 2 , root mean square error (RMSE), mean absolute percentage error (MAPE) and normalized BIC (Bayesian information criterion). predictive model is useful at 95% confidence limits 35 . On the basis of the above discussion, it can be concluded that the model is performing satisfactory for all the single-noise metrics.…”
Section: Time-series Analysis Via Arimamentioning
confidence: 99%
See 1 more Smart Citation
“…Several measures of accuracy were applied to ascertain the performance of the ARIMA models so developed such as stationary R 2 , R 2 , root mean square error (RMSE), mean absolute percentage error (MAPE) and normalized BIC (Bayesian information criterion). predictive model is useful at 95% confidence limits 35 . On the basis of the above discussion, it can be concluded that the model is performing satisfactory for all the single-noise metrics.…”
Section: Time-series Analysis Via Arimamentioning
confidence: 99%
“…Schomer et al 30 simulations demonstrate that nonconsecutive sampling strategies reduce the overall sampling requirements for non stationary data. The exhaustive literature review reveals that ARIMA methodology has not been implemented so far for long-term noise monitoring, although it has been extensively used in air and water pollution predictions [32][33][34][35][36] . The present work extends Kumar and Jain 34 utilizing the ARIMA approach for time-series predictions and forecasting of traffic noise levels.…”
Section: Introductionmentioning
confidence: 99%
“…In the world, and especially in India, river water is the main source for all anthropogenic activities such as drinking, irrigation and agriculture (Parmar and Bhardwaj 2014;Herojeet et al 2016).The river water quality is getting degraded day by day, and water pollution is the main reason for degradation in the recent years. The water is getting polluted mainly because of rapid industrialization of river basins and river Krishna is also one among them.…”
Section: Introductionmentioning
confidence: 99%
“…These pollutants alter the physio-chemical characteristics of aquatic ecosystem because it has high concentration of BOD and TDS which cause rapid depletion of oxygen in water. It is estimated that every year, millions of tons of waste in the form of industrial waste, agricultural waste and urban waste water is dumped into the river, thus making the water from the river unusable and requires frequent quality checks (Shah and Joshi 2017;Kaur et al 2017;Parmar and Bhardwaj 2014;Loganathan and Ahamed 2017). In India, the water quality check is carried under the careful monitoring of Central Pollution Control Board (CPCB) (Nagar 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation